Copy Number Variation Distribution in Six Monozygotic Twin Pairs Discordant for Schizophrenia. (April 2014) - Castellani, Christina A.; Awamleh, Zain; Melka, Melkaye G.; O'Reilly, Richard L.; Singh, Shiva M.
<x content-type="archive" xml:space="preserve">Abstract</x> We have evaluated copy number variants (CNVs) in six monozygotic twin pairs discordant for schizophrenia. The data from Affymetrix® Human SNP 6.0 arrays™ were analyzed using Affymetrix® Genotyping Console™, Partek® Genomics Suite™, PennCNV, and Golden Helix SVS™. This yielded both program-specific and overlapping results. Only CNVs called by Affymetrix Genotyping Console, Partek Genomics Suite, and PennCNV were used in further analysis. This analysis included an assessment of calls in each of the six twin pairs towards identification of unique CNVs in affected and unaffected co-twins. Real time polymerase chain reaction (PCR) experiments confirmed one CNV loss at 7q11.21 that was found in the affected patient but not in the unaffected twin. The results identified CNVs and genes that were previously implicated in mental abnormalities in four of the six twin pairs. It included PYY (twin pairs 1 and 5), EPHA3 (twin pair 3), KIAA1211L (twin pair 4), and GPR139 (twin pair 5). They represent likely candidate genes and CNVs for the discordance of four of the six monozygotic twin pairs for this heterogeneous neurodevelopmental disorder. An explanation for these differences is ontogenetic de novo events that differentiate in the monozygotic twins during development.